Pengembangan Dashboard Monitoring dan Pengingat Imunisasi Balita dengan Metode Scrum - Bakhtiyar Hadi Prakoso; Gandu Eko Julianto Suyoso; Veronika Vestine; Muhammad Yunus (Puslitbang Sinergis Asa Professional, 2026)
The national coverage rate for complete basic immunization in Indonesia is high. However, several regions in Indonesia have under-performed targets. Several factors contribute, including a lack of parental awareness of the importance of immunization, suboptimal program planning and management, and manual recording processes. These factors contribute to inaccurate decision-making. This research aims to create a dashboard system for monitoring and reminding toddlers about immunizations for decision support systems. The system development method used was the Scrum method. The results indicate that this system meets the standard requirements for immunization monitoring. Further development of the system can include the addition of a web service feature to facilitate access across multiple platforms.